2005
DOI: 10.1016/j.jvs.2004.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Inoue single-branched stent-graft implantation for thoracic aortic aneurysm or dissection involving the left subclavian artery: Short- to medium-term results in 17 patients

Abstract: The results demonstrate the feasibility of the Inoue single-branched stent graft for thoracic aortic aneurysms or dissections involving the left subclavian artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 17 publications
0
44
0
1
Order By: Relevance
“…Some studies have reported favorable results using fenestrated/branched techniques in aortic arch pathologies. [3][4][5][6][7] However, this approach is limited by the morphological diversity of the aortic arch, necessitating patient-specific and tailor-made devices. Moreover, the procedures are complex and time-consuming, often inapplicable in emergency situations, and place a considerable financial burden on the patient, limiting their clinical usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported favorable results using fenestrated/branched techniques in aortic arch pathologies. [3][4][5][6][7] However, this approach is limited by the morphological diversity of the aortic arch, necessitating patient-specific and tailor-made devices. Moreover, the procedures are complex and time-consuming, often inapplicable in emergency situations, and place a considerable financial burden on the patient, limiting their clinical usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al recently reported improved results without any stroke complication using a single-branched stent graft for distal aortic arch aneurysm. 16 If limited to an indication for stent-grafting only from zone 2, a branched-stent graft seems to be an acceptable procedure. However, as we report, more than one-third of cases of distal aortic arch disease need a more proximal landing from zone 1 at least.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on handmade SGs are limited, and the results in these cases are unknown. [15][16][17][18][19][20][21][22][23] In Japan, EVR devices have not been approved as medical devices thus far. Therefore some medical institutions produce their own handmade SGs, and compared with other countries, only a small number of patients undergo this procedure in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, both the materials used to prepare the SGs and the procedure followed for EVR vary, and the clinical results are influenced by the institutional indications and techniques. 1,[16][17][18][19][20] Our department has been producing and using SGs that comprise stainless steel Z stents and are covered with an ultrathin-wall woven polyester fabric. The initial and midterm results for repair using these handmade SGs for thoracic and abdominal aortic diseases in high-risk patients are considered to be satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation